AD-RPG: elicitando requisitos na idade média por meio de um jogo educacional adaptativo - Lemos, Eduardo Luis (2018)
The software development process has essential steps that must be well executed to avoid extra costs. One of these steps is the Requirements Elicitation, which captures the features of the product. However, the learning of this stage by the developers presents a deficit through the "standard" system of teaching. In order to complement this learning the use of educational games is an option, offering more practical and exploratory teaching methods. Still the use of learning styles has been growing and bringing a more natural learning. The aim of this work is to integrate educational games with learning styles, seeking a teaching environment that aims to bring the student a natural and comfortable approach to learning in their own way. It aims to create an adaptive game to the user's learning style for teaching requirements surveying, where students venture into a medieval world while learning requirements surveying techniques, and the concepts of functional and non-functional requirements, while providing an educational and playful activity. As a model of style used, we chose the ISL model, which brings four main groups of styles. In order to evaluate the game, two test steps were performed, the first one with the game incomplete, seeking to evaluate points related to the game itself and to obtain suggestions for improvements. The second stage consisted of the application of the complete game, and also added some of the suggestions received in the previous test. The game was applied to under-graduate students of the courses of Computer Science, Information Systems and Computer Engineering, in Federal University of Santa Maria. For the information capture and evaluation of the game was used the model MEEGA+, an evaluation model development specifically for educational games. Positive results were obtained regarding the appearance of the game, and the learning potential presented, in which students considered the game relevant to their learning and which helped in the understanding of the contents addressed. However, there is still a need for improvements related to the protection of user errors and sources of teaching materials, in addition to expanding the content covered.